UV-induced alleviation of K-specific restriction of bacteriophage lambda. - Day, R S (1977)
A partial release of K-specific restriction of phage lambda grown in Escherichia coli C was observed when E. coli K strains AB1157 (having wild-type repair of UV-produced DNA damage) and AB1886 (uvrA) were irradiated with UV light before infection. The effect occurred in AB1886 at lower UV fluences than it did in AB1157. Little or no release of restriction was observed when AB2463 (recA) or AB2494 (lex-1) was used. Such release of restriction appears to be another of the UV-induced phenomena associated with "SOS" repair.